President's Speech for Career Fair 2010 - Prof. Dr. Zaharin Yusoff (Multimedia University, 2010)
This was the welcoming speech addressed by MMU President, Prof. Dr. Zaharin bin Yusoff during Career Fair 2010. The Career Fair 2010 is organised by STAD, Accounting Week Team, and Career Fair Team.